Cultura y comportamiento organizacional de la cooperativa de ahorro y crédito occidental de la ciudad de Latacunga. - Murgueitio Segovia, Gabriela Alexandra (2023)
Analyzing and strengthening the cultural elements and characteristics is essential to improve the well-being and promote the development and growth of the Occidental Cooperative, located in the city of Latacunga. The research work, entitled "Culture and Organizational Behavior in the Occidental Cooperative of the City of Latacunga" has as its main objective to develop a general plan of culture and used, analyzing the collected numerical data to determine the current situation of the cooperative in terms of its organizational culture. The research used the Denison Test and the Job Satisfaction Test SL-ARG. The Spearman's statistical analysis identified, positively high, positively moderate, and negative correlations according to the dimensions established in the Likert scale. Even though the sample was small, consisting of 8 workers from the branch in the city of Latacunga, it is important to mention that Cronbach's Alpha coefficient was applied in the SPSS software to validate the reliability of the instrument, obtaining a value of 0, 82. To make a meaningful contribution to the Occidental Cooperative, the inquiry identified the critical elements for the creation of strategies and the General Plan of Culture and Organizational Behavior.